2022
DOI: 10.1096/fj.202200765r
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide nanoliposomes augment the efficacy of venetoclax and cytarabine in models of acute myeloid leukemia

Abstract: Despite several new therapeutic options for acute myeloid leukemia (AML), disease relapse remains a significant challenge. We have previously demonstrated that augmenting ceramides can counter various drug-resistance mechanisms, leading to enhanced cell death in cancer cells and extended survival in animal models. Using a nanoscale delivery system for ceramide (ceramide nanoliposomes, CNL), we investigated the effect of CNL within a standard of care venetoclax/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Long-chain ceramides, such as C16-ceramide, may be more cytotoxic than very long-chain ceramides, such as C24:1-ceramide [29]. We previously demonstrated that elevated C16/C24:1 ceramide ratios are associated with increased cell death [11]. LCL-805 increased both C16- and C24:1-ceramides ( Figure 2E, F ) and C16/C24:1 ceramide ratios ( Figure 2G, H ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Long-chain ceramides, such as C16-ceramide, may be more cytotoxic than very long-chain ceramides, such as C24:1-ceramide [29]. We previously demonstrated that elevated C16/C24:1 ceramide ratios are associated with increased cell death [11]. LCL-805 increased both C16- and C24:1-ceramides ( Figure 2E, F ) and C16/C24:1 ceramide ratios ( Figure 2G, H ).…”
Section: Resultsmentioning
confidence: 90%
“…The development of ceramide-generating therapeutics is an enticing antineoplastic strategy as ceramides are important mediators of cell death and cancer cells modulate ceramide catabolism to maintain survival. Elevating intracellular ceramides through exogenous supplementation [10, 11] or metabolic blockade [12, 13] are actively being explored as anticancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should confirm these findings and investigate the pharmacologic vulnerabilities of the two sphingolipid subtypes. Given the promise of targeting sphingolipid metabolism in AML 7,23,24 , we envision that sphingolipidomic subtyping could contribute to tailored treatment selections for AML patients that otherwise lack targetable alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several studies have tried to better understand the role of OXPHOS [ 110 ], mitochondrial respiration [ 111 ], amino acids [ 112 ], and lipids such as fatty acids [ 113 , 114 , 115 , 116 ], nicotinamide [ 117 ], and ceramide [ 118 , 119 ], in VEN response. It is likely that a better understanding of the integrated stress response (ISR) mediated by the ATF4 transcription factor will help to fill the gap between cell death, metabolism, and VEN resistance [ 46 , 91 , 106 , 120 ].…”
Section: Non-genetic Factors Driving Venetoclax Efficacymentioning
confidence: 99%